(untitled) (International Journal of Pharmacy and Life Sciences, 2012)
The present manuscript describe simple, sensitive, rapid, accurate, precise and cost effective First derivative spectrophotometric zero crossing point method for the simultaneous determination of Valsartan and Hydrochlorthiazide in combined dosage form. The utility of first derivative data processing program is its ability to calculate unknown concentration of components of interest in a mixture containing an interfering component. The first order derivative absorption at 250.20 nm (zero cross point of Valsartan) was used for Hydrochlorthiazide and 270.60 nm (zero cross point of Hydrochlorthiazide) was used for Valsartan. The linearity was obtained in the concentration range of 4-20 μg/ml for Valsartan and 2-14 μg/ml for Hydrochlorthiazide. The method was successfully applied to pharmaceutical dosage form because no interference from the mixture excipient was found. The suitability of this method for the quantitative determination of Valsartan and Hydrochlorthiazide was proved by validation. The proposed methods were found to be simple and sensitive for the routine quality control application of Valsartan and Hydrochlorthiazide in pharmaceutical dosage form. The results of analysis have been validated statistically and by recovery studies.